Design of an automated data entry system for hand-filled forms - Lim, Woan Ning; Yap, Keem Siah; Khalid, Marxuki; Yusof, Rubiyah (2000)
In this new informative era, data and information is the most important asset to organizations. A large amount of money and manpower have been spent in data gathering, data entry, and storage every year. In Malaysia, data gathering is still largely done through manually filled forms. This data is then entered and stored into databases in government and private organizations manually. Such mode of data entry and storage requires a lot of manpower and is time consuming. At the Centre for Artificial Intelligence and Robotics (CAIRO) of Universiti Teknologi Malaysia, research is being carried out to design a system for automated data entry of handwritten-filled forms. The system consists of a high-speed scanner with an autofeeder and a computer. In the first phase, software was developed that allows the user to design the template of existing forms such that only the regions of interests are captured. The next phase involved the design of software to capture handwritten characters in the regions of interest through the scanned forms. Image processing techniques are then used to filter and improve the image of the scanned handwritten characters before they are recognized using a neural network algorithm. Once the characters are identified and verified, they are automatically stored into a database. This system can be used efficiently in many organizations that involve gathering and processing of a large number of data such as the National Registration Department, Survey Research Malaysia, Kementerian Pendidikan and Lembaga Hasil Dalam Negeri.